Ushul Fiqh, Qaidah Fiqhiyyah, and Islamic Jurisprudence: A Review - Nadiyah Mu’adzah (SMART Insight, 2022)
This study aims to determine previous research trends on fiqh principles, assess the relationship of research collaboration, and identify future research directions. It uses 101 articles published between 20014-2022 about principle fiqh in Dimensions. Using a qualitative and quantitative approach, the Bibliometric method and Systematic Literature Review (SLR). This study uses VosViewers software to process the data that has been collected with the result that can be analyzed. It is known that five sub-themes dominate the research related to fiqh principles: the position of fiqh rules in Islamic law, the implementation of the application of fiqh rules to DSN-MUI fatwas the impact and important role of fiqh rules on muamalah. discusses how to use the rules of fiqh in muamalah, an overview and classification of fiqh rules, and the relationship between fiqh rules and ushul fiqh and ushul rules. This study can be used as a reference in identifying influential authors, articles, journals, and countries so researchers will find it easier to find references that have a significant impact on the development of the fiqh rule literature. This result can also imply the regulator to re-evaluate regarding improving the quality and quantity of the application of fiqh principles to the fatwas produced. Expected that researchers, practitioners and regulators will walk side by side to improve implementation and literature about fiqh rules for the future.